Summary and Evaluation of the EDEN ISS Public Outreach Activities - Zabel, Paul; Zeidler, Conrad; Vrakking, Vincent; Schubert, Daniel; Imhof, Barbara; Hogle, Molly (2020)
EDEN ISS is a European project focused on advancing bio-regenerative life support systems, in particular plant cultivation in space. A mobile test facility was designed and built between March 2015 and October 2017. The facility incorporates a Service Section which houses several subsystems necessary for plant cultivation and the Future Exploration Greenhouse. The latter is built similar to a future space greenhouse and provides a fully controlled environment for plant cultivation. The facility was setup in Antarctica in January 2018 and successfully operated between February and November of the same year. During that nine month period around 270 kg of food was produced by the crops cultivation in the greenhouse. It is the wish and more often the need for scientific projects to communicate their outcomes not only to the scientific community, but also to the general public. The EDEN ISS project and in particular the experimental phase in Antarctica was accompanied by extensive public outreach activities. Presence in social media, a project website, informative flyers, an experimental toolkit for young students were created in order to engage with the general public. This paper describes the different public outreach activities of the project and also evaluates their effectiveness. For the evaluation, statistics from the website and social media accounts as well as responses to press releases and educational activities are being displayed. Based on the experience from the outreach campaign of EDEN ISS, the paper provides recommendations on how to organize and conduct public outreach activities for scientific projects in space exploration